Controlling Catenation in Germanium(I) Chemistry through Hemilability. (9th June 2021) - Caise, Alexa; Griffin, Liam P.; Heilmann, Andreas; McManus, Caitilín; Campos, Jesús; Aldridge, Simon
Abstract: We present a novel approach for constructing chains of Group 14 metal atoms linked by unsupported metal–metal bonds that exploits hemilabile ligands to generate unsaturated metal sites. The formation/nature of catenated species (oligo‐dimetallynes) can be controlled by the use of (acidic/basic) "protecting groups" and through variation of the ligand scaffold. Reduction of Ar NiPr2 GeCl (Ar NiPr2 =2, 6‐( i Pr2 NCH2 )2 C6 H3 )—featuring hemilabile N i Pr2 donors—yields (Ar NiPr2 Ge)4 (2 ), which contains a tetrameric Ge4 chain. 2 represents a novel type of a linear homo‐catenated Ge I compound featuring unsupported E−E bonds. Trapping experiments reveal that a key structural component is the central two‐way Ge=Ge donor‐acceptor bond: reactions with IMe4 and W(CO)5 (NMe3 ) give the base‐ or acid‐stabilized digermynes (Ar NiPr2 Ge(IMe4 ))2 (4 ) and (Ar NiPr2 GeW(CO)5 )2 (5 ), respectively. The use of smaller N ‐donors leads to stronger Ge‐N interactions and quenching of catenation behaviour: reduction of Ar NEt2 GeCl gives the digermyne (Ar NEt2 Ge)2, while the unsymmetrical system Ar NEt2 GeGeAr NiPr2 dimerizes to give tetranuclear (Ar NEt2 GeGeAr NiPr2 )2 through aggregation at the N i Pr2 ‐ligated Ge I centres. Abstract : A new approach for the rational construction of chains of Group 14 metal atoms linked by unsupported metal–metal bonds is reported, which exploits hemilabile ancillary ligands to generate unsaturated metal sites. The resulting oligo‐dimetallyne chains feature alternating single and double metal–metal bonds.